Giant-Cavity-Based Quantum Sensors With Enhanced Performance - Zhu, Y. T.; Wu, R. B.; Peng, Z. H.; Xue, Shibei (Frontiers in Physics, 2022)
Recent progress has revealed that quantum systems with multiple position-dependent couplings, e.g., giant atoms, can exhibit some unconventional phenomena, such as non-exponential decay, etc. However, their potential applications are still open questions. In this paper, we propose a giant-cavity-based quantum sensor for the first time, whose performance can be greatly enhanced compared to traditional cavity-based sensors. In our proposal, two cavities couple to a dissipative reservoir at multiple points while they couple to a gain reservoir in a single-point way. To detect an unknown parameter entering the sensor, a waveguide is coupled to one of the cavities where detecting fields can pass through for homodyne detection. We find that multiple position-dependent couplings can induce an inherent non-reciprocal coupling between the cavities, which can enhance the performance of sensors. Compared to the results in Ref. [Lau2018], our output noise can remain at the shot noise level, which is about one order of magnitude lower. Besides, the signal-to-noise ratio per photon is also enhanced by about one order of magnitude. These results show that the multiple-point-coupling structure is beneficial to existing quantum devices.